The Implementation of Village Funds and the Reproduction of Local Elite Power in Village Governance and Accountability in Indonesia - Siti Marwiyah; Gilang Firman Prasetyo; Yunita Apriliani; Diki Wahyudi (The Future of Education Journal, 2026)
The Village Fund policy, which is based on Law Number 6 of 2014, represents a form of fiscal decentralization from the central government to villages aimed at promoting equitable development and improving community welfare. This study aims to examine the implementation of Village Funds, analyze the practices of local elite domination in their management, and evaluate the application of village governance and accountability principles. The study employed a descriptive qualitative method with a library research approach and was analyzed using the theories of elite capture and power reproduction proposed by Pierre Bourdieu. The findings indicate that the administrative implementation of Village Funds has generally followed existing procedures and contributed to infrastructure development and community empowerment in rural areas. However, in practice, the dominance of local elites is still evident through control of information, influence in village deliberations, and patronage relationships that strengthen certain power positions. On the other hand, the principles of transparency, participation, and accountability have been implemented normatively, yet their application remains suboptimal due to limited access to information, low levels of public understanding, and weak supervisory functions. Therefore, Village Funds function not only as instruments of rural development but also as spaces for the reproduction of local elite power. Consequently, strengthening community participation, improving transparency, and reforming village institutions are necessary to ensure that Village Fund management becomes more democratic and accountable.